Integrasi Sustainable Development Goals dalam Rencana Kerja Pemerintah Desa Popalia - Ulandari, Ulandari; Azhari, Azhari; Hidayat, Rahmat (SIGn Journal of Social Science, 2023)
This research aims to analyze the integration of SDG values into the Popalia Village Government Work Plan. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that integrating the SDGs into the Popalia Village Government Work Plan has significantly contributed to village development. At the input stage, the active participation of the community in formulating work programs has reflected an inclusive approach that considers the needs and aspirations of the residents. In terms of outputs, tangible progress has been made in developing village infrastructure and health services, although some programs have yet to materialize fully. The impact of the Village Government Work Plan implementation has been positively felt by the community, especially in improving road infrastructure which enhances access and mobility. These results show that the integration of SDGs into the Popalia Village Government Work Plan has successfully created changes impacting the community’s quality of life. However, there are still challenges to overcome for more comprehensive success. Therefore, it is recommended that the Popalia Village Government intensify efforts to complete the unimplemented Village Government Work Plan programs, prioritizing initiatives that directly impact improving the community’s quality of life. Relevant community organizations are expected to support the village government through collaboration and mobilizing additional resources to ensure the sustainability and expansion of programs aligned with the SDGs. The villagers are also encouraged to actively participate in every stage of the Village Government Work Plan, from planning to evaluation, to ensure that the initiatives align with their needs and aspirations. Enhancing communication and coordination among all stakeholders is vital to overcoming existing challenges and maximizing the positive impact of integrating SDGs into the development of Popalia Village.